Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3354/meps10344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an offshore wind farm on temporal and spatial patterns in the demersal fish community

Abstract: The rapid increase in offshore wind energy worldwide has raised concern about its potential risks to marine biodiversity due to habitat alteration, disturbance from noise and electromagnetic fields. This study presents results of surveillance studies performed at the Lillgrund wind farm in Sweden to investigate the integrated effects of these factors on the abundance and distribution patterns of benthic fish communities. The studies revealed no large-scale effects on fish diversity and abundance after establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 35 publications
7
68
0
3
Order By: Relevance
“…In particular, the opportunities to catch valuable species would be considerably reduced. However, other studies indicated that, within a time window of seven years after construction, the studied offshore wind farm showed neither a direct benefit nor a definite threat to fish diversity [58] as well as sandeels and their sand habitat [59].…”
Section: Marine Speciesmentioning
confidence: 99%
“…In particular, the opportunities to catch valuable species would be considerably reduced. However, other studies indicated that, within a time window of seven years after construction, the studied offshore wind farm showed neither a direct benefit nor a definite threat to fish diversity [58] as well as sandeels and their sand habitat [59].…”
Section: Marine Speciesmentioning
confidence: 99%
“…In this sense, the shipwreck site could be considered as a platform for the study of the surrounding environment and its complex dynamic system as this will further facilitate the abilities for future investigation and conservation of the wreck (Church et al, 2007;Brennan et al, 2011). The findings from this study may have specific implications for artificial reefs and be used to discuss the potential effects of intentionally sinking ships or other objects to the seabed to serve as artificial reefs (Ambrose and Anderson, 1990;Baine, 2001) or marine underwater constructions such as bridges, piers, breakwaters and fundaments for offshore wind farming (Bergström et al, 2013(Bergström et al, , 2014.…”
Section: Introductionmentioning
confidence: 89%
“…Juvenile recruitment of Atlantic cod has also been observed at wind farms in the Belgium part of the North Sea [87]. Changes in prey densities may also be masked by predation rates [65,88], and will potentially strengthen predator avoidance behaviors like diel migration, further complicating the relationship between attraction-production dynamics [77]. While the mechanics of fish abundance at OWFs is not yet fully understood and requires additional analysis, it is becoming increasingly obvious that any ecological benefits will only be attained if fishing practices are banned within the wind farms [89].…”
Section: Potential Effects On Mediterranean Fish Communitiesmentioning
confidence: 97%
“…For Mediterranean fish species, it is difficult to state the effects based on the findings of Northern European studies as there is a limited availability of information, and the majority of existing monitoring programs focus on species that are not generally present in Mediterranean waters, e.g., Atlantic cod [82,85,88]. That being said, there is evidence that suggests a yield increase of fish populations at wind farms as opposed to the simple attraction model previously hypothesized [85,86].…”
Section: Potential Effects On Mediterranean Fish Communitiesmentioning
confidence: 99%